CESifo World Economic Survey August 2008 - Gernot Nerb; Anna Stangl (CESifo World Economic Survey, 2008)
World Economic Climate: World Economic Climate deteriorates further - Economic Expectations: Assessments of the current economic situation and economic expectations downgraded - Inflation: Rising inflation expected in 2008 - Interest Rates: Interest rates expected to rise - Currencies: US dollar remains undervalued - Special Topic: Energy prices
Keywords: 330